The Role of Digital Marketing in Expanding Market Access for Local Agribusiness Products - Malta (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2026)
Limited market access remains a major challenge facing local agribusinesses, primarily due to reliance on conventional marketing channels and a weak bargaining position within the marketing chain. Advances in digital technology present new opportunities for agribusinesses to transcend geographic boundaries, expand consumer reach, and increase product visibility amidst increasingly competitive markets. However, the utilization of digital marketing has not been fully optimized due to the impact of internal business capacity and the structural dynamics of the agribusiness market itself. This study aims to analyze the role of digital marketing in expanding market access for local agribusiness products and encouraging market inclusion and a desire to do business. This study uses a qualitative approach, reviewing and analyzing various scientific literature sources and previous research relevant to the theme of digital marketing and local agribusiness. The results indicate that digital marketing serves as an alternative channel capable of expanding market reach and strengthening interactions between agribusinesses and consumers. The effectiveness of digital marketing utilization depends heavily on the readiness, ability, and experience of agribusinesses in consistently managing digital channels. In the medium to long term, digital marketing has the potential to drive broader market inclusion and support local agribusiness aspirations by increasing income stability and strengthening business actors' positions within the market structure.